2019
DOI: 10.1016/j.gde.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical regulation of local chromatin structure

Abstract: DNA in higher eukaryotes is packaged with histone proteins to form nucleosomes which are further assembled into higher-order chromatin fibres to protect and regulate access to the genetic information. Chromatin folding above the nucleosomal level is controversial with differing views proposing unfolded irregular structures through to highly organised chromatin fibres. Using a combination of techniques including sedimentation studies, electron microscopy and super-resolution imaging views are converging to indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 76 publications
2
9
0
Order By: Relevance
“…Recent whole-genome sequencingbased studies have indeed revealed the depletion of nucleosomes at many promoter and enhancer regions to accommodate transcription (9,10). In addition, nucleosome positioning may affect gene expression indirectly by regulating higher-order chromatin organization (11)(12)(13)(14). For example, protein molecules such as Cohesin and CTCF have been shown to facilitate chromatin folding and the formation of socalled topologically associated domains (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Recent whole-genome sequencingbased studies have indeed revealed the depletion of nucleosomes at many promoter and enhancer regions to accommodate transcription (9,10). In addition, nucleosome positioning may affect gene expression indirectly by regulating higher-order chromatin organization (11)(12)(13)(14). For example, protein molecules such as Cohesin and CTCF have been shown to facilitate chromatin folding and the formation of socalled topologically associated domains (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…In higher eukaryotes, DNA is packaged into chromatin that is organized as chromosomes in the nucleus (Gilbert 2019). The organization and regulation of chromatin architecture has been studied for many years, because chromatin structure plays an important role in gene expression and genome integrity.…”
Section: A New View Of Chromatin Behaviormentioning
confidence: 99%
“…This remains an interesting topic, firstly, because, inside the densely populated chromatin space of the nucleoplasm, the kinetics of topoisomerase-binding to waves of (+) supercoiling are not well understood. Second, the conformations that a transiently (+) supercoiled chromatin fiber generated by a translocating replisome may adopt remain elusive [ 51 ]. Third, topoisomerase action always requires DNA strand breakage, which must occur either at some distance ahead of an approaching replisome in order to avoid catastrophic collisions, or demands replisome pausing during topoisomerase action.…”
Section: Established Solutions At Topologically Stressed Replicatimentioning
confidence: 99%
“…TOP1B finds its substrate in the form of double-stranded DNA crossings [ 56 ], which is a key feature of plectonemic supercoiled DNA [ 23 ]. However, whether transiently (+) supercoiled chromatin fibers adopt a similar interwound structure has not been established [ 51 ]. In any case, diffusion-controlled search modes would imply that a certain level of recognizable (+) chromatin supercoiling must have been generated by a replisome.…”
Section: Established Solutions At Topologically Stressed Replicatimentioning
confidence: 99%